2022
DOI: 10.1002/aic.17954
|View full text |Cite
|
Sign up to set email alerts
|

Readily processed multifunctional SiC catalytic filter for industrial emissions control

Abstract: One step fabrication of SiC catalytic filter is currently limited by the mismatched calcination temperature between SiC filter (>1700 C) and the catalysts (<800 C), and the difficulty in the chemical immobilization of catalysts. Here, a SrTi 1Àx Co x O 3 -SiC (STC-SiC) catalytic filter was directly fabricated from raw SiC grains and STC precursor oxides (SrCO 3 , TiO 2 , and Co 3 O 4 ) via a single-step reactive thermal processing (SRTP) approach, which significantly reduced energy consumption and sintering ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…In our previous work, we found that the acid‐treating process can construct Co 3 O 4 nanoparticles on STC in the STC‐SiC catalytic membrane through a surficial reconstruction process 35 . Herein, the acid‐treating process was also conducted to generate Co 3 O 4 nanoparticles in the TCS catalytic membrane.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, we found that the acid‐treating process can construct Co 3 O 4 nanoparticles on STC in the STC‐SiC catalytic membrane through a surficial reconstruction process 35 . Herein, the acid‐treating process was also conducted to generate Co 3 O 4 nanoparticles in the TCS catalytic membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported the successful fabrication of multifunctional disc-shaped SrTi x Co 1Àx O 3 -SiC (STC-SiC) catalytic membrane through a single-step reactive thermal processing (SRTP) approach. 35 The STC-SiC catalytic membrane exhibits prominent PM 2.5 filtration and NO oxidation efficiencies compared to other reported counterparts at high temperatures. Here, we report the fabrication of a high-performance tubular Co-SiC (TCS) catalytic membranes, with an effective area of about 226 cm 2 , for simultaneous removal of PM 2.5 , NO, and toluene through combined cold isostatic pressure molding, spin spray-coating of the separation layer and acid-treating processes.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations